Architecture and Art Regulations for Karl Marx Street - Mironenko, Alla (project baikal, 2015)
The architecture and art regulations for Karl Marx Street and adjoining territories have been worked out for the Committee for town planning of the Irkutsk city administration. Basic provisions: facades of buildings and structures, outdoor advertising and information facilities, artistic illumination of buildings, elements of land improvements. The main principle is to preserve historical appearance and to create a contemporary and comfortable environment.
Keywords: Karl Marx Street; Bolshaya; architectural and art decision; objects of cultural heritage; facades; land improvement